Analysis of Visitor Satisfaction at the Samudera Pasai Islamic Museum Tourist Attraction Using the Servqual Method - Nazarta Sinaga, Dearma Fahri; Fatimah, Fatimah; Sayuti, Muhammad (Malikussaleh University, Aceh, Indonesia, 2024)
Visitor satisfaction greatly influences the development of the tourism industry, the development of the tourism industry in a region will give birth to other supporting businesses. The Samudera Pasai Islamic Museum is one of the cultural-based tourist attractions that displays tourist attractions in the form of fine art, historical relics and customs. The Samudera Pasai Islamic Museum is located in North Aceh Regency, Aceh Province. In 2023, the average number of museum visitors was 1,050 people and there was a significant decrease in visitors in September 2023. The purpose of this study was to determine visitor satisfaction with the quality of service provided by the management of the Samudera Pasai Islamic Museum. The method used in this study is the Service Quality (Servqual) method. Servqual is a method used to identify the level or quality of visitor satisfaction with the services provided by a service industry through five dimensions, namely tangibles (physical evidence), responsiveness, reliability, empathy and assurance by analyzing the gap between the value of perception and the value of visitor expectations. The results of the study showed that in the tangibles dimension, the gap value was obtained at -0.50, the responsiveness dimension obtained a gap value of -0.43, the reliability dimension obtained a gap value of -0.32, the assurance dimension obtained a gap value of -0.26 and the empathy dimension obtained a gap value of -0.34. These results indicate that the satisfaction of visitors to the Samudera Pasai Museum has not been achieved, so service improvements are needed